Collective density fluctuations and dynamics of ions in water studied by the interaction-site model of liquids - Hirata, F.; Chong, S.-H. (Condensed Matter Physics, 2001)
The collective excitations in water are studied based on the interactionsite model of liquids. Three collective modes, extracted from a generalized Langevin equation combined with the RISM theory of liquids, are identified as an acoustic mode and two optical modes. The drag force exerted on ions in water is described in terms of the response of these solvent collective excitations to the perturbation of ions. The ion-size dependence of the drag force, which has been a central issue in physical chemistry for long time, is studied in molecular detail based on the novel approach.